Analisis Sosiologi Sastra Monolog “Perahu Kecil Anita” Karya SMAN 1 Bangsal (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Literary works are said to be products of human creativity that reflect life, cultural values, and the perspectives of society. Through literary works, writers attempt to convey messages, concepts, and ideas that originate from social and imaginative experiences. Literary works can take the form of prose, poetry, or drama. One form of literary work that is interesting to study sociologically is dramatic literature in the context of monologues. One monologue that is interesting to study is a monologue by a student of SMAN 1 Bangsal entitled “Anita's Little Boat.” This study aims to examine the monologue entitled “Anita's Little Boat” performed by a student at SMAN 1 Bangsal through a sociological approach to literature. This study uses a descriptive qualitative method using Karl Marx's theory to analyze the relationship between the content of the monologue and the social context. The information collection method used observation and note-taking. The results of the analysis show that through a sociological approach to literature and Karl Marx's class theory, this monologue presents social criticism that raises issues of alienation, inequality of ownership, and exploitation, while also presenting an initial awareness of the possibility of social change or revolution. The monologue also illustrates how class ideology can perpetuate injustice and restrict social mobility, as well as strengthen the dominance of the ruling class.